Different approaches for genetic improvement of sesame (Sesamum indicum L.) for enhancing yield in India: A Review: APPROACHES FOR GENETIC IMPROVEMENT OF SESAME FOR ENHANCING YIELD IN INDIA: A REVIEW - DINKAR; SIMA SINHA; ALPANA KUMARI SINGH; KHUSBOO CHANDRA; TAPASH DAS GUPTA (Journal of Oilseeds Research, 2024)
Sesame (Sesamum indicum L., 2n=2x=26) is an important oilseed crop from family Pedaliaceae, grown widely in Asia and Africa. Polyunsaturated fatty acids (PUFA), proteins, lignans (sesamin and sesamolin), and tocopherol all are present in high concentrations in sesame seed oil. The sesame crop is termed as queen of oilseeds because of its high oil quality and presence of lignans which prevent rancidity. Unavailability ofstable genotypes with high yield, presence of wild traits like non-shattering capsule, indeterminate growth habit and asynchronous capsule ripening are the major constraints in sesame. To overcome these yield limiting conditions, integrated breeding approach like conventional plant breeding alongwith non-conventional methodssuch as mutation breeding, marker assisted breeding, transgenic technology and genome editing are to be followed. In recent time, Marker Assisted Selection with detailed information on genomic resources has new challenges to strengthen the approach for betterment of sesame productivity genome editing techniques can also help in improving different desirable characters. The review highlights several scientific research works conducted for sesame genetic improvement including both traditional and modern thoughts.